TVT versus TOT in the treatment of female stress urinary incontinence: a systematic review and meta-analysis - Huang ZM; Xiao H; Ji ZG; Yan WG; Zhang YS (Dove Medical Press, 2018)
Zhong-Ming Huang, He Xiao, Zhi-Gang Ji, Wei-Gang Yan, Yan-Sheng Zhang Department of Urology, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing 100730, China Background: To evaluate the evidence available on the effects and safety of tension-free vaginal tape (TVT) versus transobturator tape (TOT) for female stress urinary incontinence therapy based on randomized controlled trials (RCTs). Methods: PubMed, Cochrane, Embase, Wanfang, China National Knowledge Infrastructure, and Weipu database were searched up to July 2017 to identify relevant studies, including qualified RCT and quite-RCT and literature sources. Relative risks (RRs), mean difference (MD), and 95% CI were calculated in our review. Result: Twenty-eight RCTs were involved in the meta-analysis with 2,505 patients in the TVT group and 2,477 patients in the TOT group. The aggregated results indicated that TOT significantly decreased the operative time (MD, −1.27; 95% CI: −1.77 to −0.76) and hospital stay (MD, −0.62; 95% CI: −1.08 to −0.17) when compared with TVT. Besides, the complications (RR, 0.86; 95% CI: 0.64–1.16) and blood loss (MD, −0.29; 95% CI: −0.71 to 0.14) were decreased in TOT but with no statistical significance; the change of VAS score (MD, 0.07; 95% CI: −0.05 to 0.19), IIQ-7 score (MD, 0.06; 95% CI: −0.03 to 0.15), and UDI-6 score (MD, 0.15; 95% CI: −0.19 to 0.48) were larger in TOT group than in TVT group, but still, with no statistical significance. However, there was no significant difference of cure rate (RR, 1.00; 95% CI: 0.96–1.04) and satisfied rate (RR, 1.00; 95% CI: 0.96–1.04) between the 2 groups. Conclusion: TOT may have more valid effects than TVT in operative time and hospital stay. Besides, TOT method showed fewer complications and blood loss than TVT, but there was no significant difference between them. The scores of VAS, incontinence impact questionnaire short form-7 (IIQ-7), and urogenital distress inventory short form-6 (UDI-6) were higher in TOT than TVT, but still no significant difference was observed. However, more studies with higher quality and larger sample size that are multicentric and have longer follow-up in the form of RCTs are warranted to confirm the current findings. Keywords: TVT, TOT, SUI, meta-analysis, randomized controlled trial